118 Functional Properties of Bifidobacterium Animalis Subsp. Lactis Cect 8145 in Canine Nutrition. (21st September 2022) - Kayser, Emanuela; He, Fei; Davenport, Gary M; de Godoy, Maria R
Abstract: The gut bacterial population has been demonstrated to influence the physiologic and metabolic functions of the host by modulating energy expenditure and immune response, therefore contributing to the health of the host. However, there is little information regarding the effects of probiotics and postbiotics on canine nutrition. The objective of this study was to evaluate the longitudinal effects of daily supplementation of Bifidobacterium animalis subsp. lactis CECT 8145 and the same strain in a heat-killed presentation (postbiotic) on weight management, fecal fermentative end-product concentration, gut hormones, postprandial glycemic and insulinemic response in overweight dogs. Thirty-six adult dogs were used in a completely randomized, double-blinded, placebo-controlled study, with 12 animals per treatment. Dogs were fed a commercial dry extruded complete and balanced diet twice daily to maintain body weight. Following a 60 d adaptation to the control diet, dogs were fed their respective treatment diets for 90 d. Treatments were provided by ADM Biopolis (Valencia, Spain) and given via gelatin capsules before morning feeding to ensure consumption of the total dose of their placebo, probiotic, or heat-killed probiotic. The treatments supplementation had no detrimental effect on the overall dog's health. Throughout the experimental period, fecal scores did not differ among dogs fed different dietary treatments (P > 0.05). However, fecal pH was significantly lower (P = 0.0049) in the dogs fed the postbiotic (5.8) compared with the group control (6.1). Greater fecal concentration of propionate (P=0.0427) was observed on dogs fed the probiotic and the dogs fed the postbiotic compared with the group control. Pancreatic polypeptide plasma concentration was less (P < 0.05) in the dogs fed the probiotic compared with treatment control. These data suggest that the longitudinal supplementation of this specific strain in the live and heat-killed presentation may interact with gut microbial fermentation and gut hormonal regulation.